2019
DOI: 10.1108/ijchm-07-2017-0431
|View full text |Cite
|
Sign up to set email alerts
|

Integrated resort employee competencies: a Macau perspective

Abstract: Purpose This study aims to develop an employee competency model for integrated resorts (IRs) in Macau through insights gleaned from IR professionals and to investigate whether any differences emerge in competency perception between IR professionals and college and high school students. Design/methodology/approach A mixed-method approach was adopted to answer the research questions. The Delphi approach was used, and four IR experts were invited to refine components of the IR competency for the survey question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Regarding other employability dimensions, there was a general pattern of agreement as well, although a closer analysis reveals some differences in perspectives. For example, practitioners deemed stress management and industry-specific professional knowledge to be critical areas wherein interns should put more effort, a result similar to that found in Qenani et al (2014) and Lou et al (2019). Conversely, interns perceived their stress management abilities to be somewhat higher than what practitioners perceived, whereas they thought their professional knowledge was lower.…”
Section: Comparison Of Perceptions On Employability (R2)mentioning
confidence: 56%
“…Regarding other employability dimensions, there was a general pattern of agreement as well, although a closer analysis reveals some differences in perspectives. For example, practitioners deemed stress management and industry-specific professional knowledge to be critical areas wherein interns should put more effort, a result similar to that found in Qenani et al (2014) and Lou et al (2019). Conversely, interns perceived their stress management abilities to be somewhat higher than what practitioners perceived, whereas they thought their professional knowledge was lower.…”
Section: Comparison Of Perceptions On Employability (R2)mentioning
confidence: 56%
“…The hospitality industry workforce is continually shifting, which creates a necessity to regularly update the understanding of good managerial characteristics. Strong work ethic and customer service orientation have been identified as crucial managerial characteristics in recent times (Lou et al, 2019). Suh et al (2012) combined the findings of previous research conducted in terms of good managerial characteristics and concluded six categories of characteristics.…”
Section: Theoretical Implicationsmentioning
confidence: 70%
“…The hospitality industry workforce is continually shifting, which creates a necessity to regularly update the understanding of good managerial characteristics. Strong work ethic and customer service orientation have been identified as crucial managerial characteristics in recent times (Lou et al , 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In line with the NPM approach, the specificities of the job and tasks dictate the employees' competencies. The literature on sectoral competency management mainly describes how to build employee competency frameworks and development programmes to align them with organizational needs (Lou et al ., 2019). Our findings on sectoral practices revealed the reverse mechanism, which leads to competency management failure.…”
Section: Discussionmentioning
confidence: 99%